Navigating Digital Frontiers: Analyzing the Strategies and Impact of Islamic Da'wah on Instagram - Ar-Ridho, Abdi; Rubino, Rubino; Madya, Efi Brata (CHANNEL: Jurnal Komunikasi, 2023)
In the wake of the digital revolution, online platforms have become pivotal arenas for religious discourse, reshaping traditional preaching methodologies. This study delves into the dynamic landscape of Islamic da'wah on Instagram, focusing on two prominent accounts, @abuazzamtv and @salaf.alummah. Leveraging a qualitative research approach, this research integrates SWOT analysis and Business Model Canvas (BMC) examination to unravel the intricacies of these accounts. The analysis unveils the strengths, weaknesses, opportunities, and threats faced by these platforms, shedding light on their unique strategies and challenges. @abuazzamtv, renowned for its extensive outreach, faces challenges in reciprocal engagement, while @salaf.alummah grapples with content format limitations. Despite these challenges, both accounts exhibit innovative approaches, including diverse content creation and active collaborations. Through strategic recommendations emphasizing interactive engagements and diverse content formats, this study offers valuable insights for enhancing the impact of online religious discourse on Instagram, fostering enduring connections in the digital age.